2022
DOI: 10.1093/nar/gkac1025
|View full text |Cite
|
Sign up to set email alerts
|

The stationary phase-specific sRNA FimR2 is a multifunctional regulator of bacterial motility, biofilm formation and virulence

Abstract: Bacterial pathogens employ a plethora of virulence factors for host invasion, and their use is tightly regulated to maximize infection efficiency and manage resources in a nutrient-limited environment. Here we show that during Escherichia coli stationary phase the 3′ UTR-derived small non-coding RNA FimR2 regulates fimbrial and flagellar biosynthesis at the post-transcriptional level, leading to biofilm formation as the dominant mode of survival under conditions of nutrient depletion. FimR2 interacts with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…The inoculated plates were incubated at 37 °C for 24 h. Antimicrobial activity was evaluated by measuring the diameter of the growth inhibition zone surrounding the disc (mm) for eight tested concentrations (from 5% to 0.039%) against the isolated strains. The following intervals of inhibition were considered: (i) no inhibition; (ii) inhibition < 12 mm: weak activity; (iii) 12 mm ≥ inhibition < 20 mm: moderate activity; (iv) inhibition ≥ 20 mm: strong activity [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…The inoculated plates were incubated at 37 °C for 24 h. Antimicrobial activity was evaluated by measuring the diameter of the growth inhibition zone surrounding the disc (mm) for eight tested concentrations (from 5% to 0.039%) against the isolated strains. The following intervals of inhibition were considered: (i) no inhibition; (ii) inhibition < 12 mm: weak activity; (iii) 12 mm ≥ inhibition < 20 mm: moderate activity; (iv) inhibition ≥ 20 mm: strong activity [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Raad et al. found that during stationary phase of E. coli , the 3’ UTR-derived FimR2 ncRNA interacted with CsrA, antagonizing its post-transcriptional functions of flagellar and fimbrial biosynthesis, and firmly strengthening the control of bacterial motility and biofilm formation ( Raad et al., 2022 ).…”
Section: Bacterial Epigenetics Mediating Antibiotic Resistancementioning
confidence: 99%
“…For instance, the teg58 ncRNA have specific interaction with argGH mRNA (arginine biosynthesis genes) to repress arginine synthesis and biofilm formation in S. aureus (Manna et al, 2022). Raad et al found that during stationary phase of E. coli, the 3' UTR-derived FimR2 ncRNA interacted with CsrA, antagonizing its posttranscriptional functions of flagellar and fimbrial biosynthesis, and firmly strengthening the control of bacterial motility and biofilm formation (Raad et al, 2022).…”
Section: Translation Suppressionmentioning
confidence: 99%
“…Most E. coli strains can form biofilms, which correlates with the multidrug resistance of E. coli isolates [21]. In 2021, Z. Naziri et al found that 99% of the E. coli isolates they studied could form biofilms in vitro [19,22]. In the same year, L. D. Buck described the genes responsible for the formation of biofilms, which can help predict the severity of UTI at the stage of laboratory screening [2].…”
Section: Introductionmentioning
confidence: 99%